Examining mental health needs of open and distance learning students: A case study of Universitas Terbuka, Indonesia - Vita Elysia; Isti Rokhiyah; Made Yudhi Setiani; Arip Priatna; Titi Chandrawati (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
The growing demand for open and distance education calls for a stronger focus on student well-being, particularly mental health. This study explores the mental health landscape at Universitas Terbuka (UT), Indonesia’s national open university, which serves a geographically dispersed and diverse student population. Employing qualitative methods, including in-depth interviews and focus group discussions (FGDs), this research aims to assess mental health needs, identify contributing stressors, and develop policy recommendations to strengthen mental health support in a distance learning context. The findings indicate that students experience anxiety, stress, and burnout, exacerbated by academic pressure, social isolation, and the absence of structured counselling services. To address these challenges, the study proposes a phased strategy: short-term awareness programs, medium-term pilot e-counselling initiatives, and long-term institutional development through a centralized mental health center. This study contributes to the field of education by offering a practical framework for integrating mental health support into distance learning environments at UT, with potential implications for similar institutions across the ASEAN region and beyond. Keywords: mental health, counselling, student, UT